Absent Sella Turcica: A Case Report and A Review of the Literature. (1st October 2013) - Paroder, Viktoriya; Miller, Todd; Cohen, M. Michael; Shanske, Alan Lawrence
<x xml:space="preserve">Abstract</x> Absent sella turcica is an extremely rare and dramatic radiographic finding. It may be isolated or occur in the presence of other anomalies, often involving the adenohypophysis. Our evaluation of a female infant with multiple anomalies including absence of the sella turcica, a normal pituitary in the craniopharyngeal canal, normal pituitary function, choanal atresia and anomalies of the appendiceal skeleton prompted a review of the occurrence and biology of an absent sella turcica.